Correlates of Adoption of Improved Apiculture Practices in Arunachal Pradesh - Mishra, B.P.; Kanwat, Manish; Gupta, B.K.; Meena, N.R.; Mishra, N.K.; Kumar, P. Suresh (Indian Journal of Extension Education, 2020)
The increasing population of India is raising alarm to search means for sufficient food for all and the employment for the young generation. The apiary or beekeeping has the potential to become the alternative of those people who needs the employment. The study was conducted in four blocks and four villages of West Siang district of Arunachal Pradesh state are selected to identify the socio-economic and personal factors affecting adoption of improved apiculture practices. The data collected from 120 respondents selected randomly revealed that the personal variable namely age, education, social participation, utilization of sources of information, mass media exposure, annual income, family type, land used, land holding and knowledge level and socio economic status correlated significantly with adoption of improved apiary practices. While correlated the age with the extent of adoption, it was negative but significant and the size of land holding was found to be negative and non significant. The statistical tests using multiple regression analysis revealed that among the variable studied, education, family type, social participation, mass media exposure, extension contact and the knowledge level were found to exhibit positively significant contribution towards adoption enhancement of apiculture practices.
Keywords: Adoption; Apiculture; Correlation; Independent; Variable